2013
DOI: 10.1242/jcs.136523
|View full text |Cite
|
Sign up to set email alerts
|

The cilium like region of theDrosophilaspermatocyte: an oncoming flagellum?

Abstract: SummaryPrimary cilia and flagella are distinct structures with different functions in eukaryotic cells. Despite the fact that they share similar basic organization and architecture, a direct developmental continuity among them has not been reported until now. The primary cilium is a dynamic structure that typically assembles and disassembles during mitotic cell cycles, whereas the sperm axoneme is nucleated by the centriole inherited by the differentiating spermatid at the end of meiosis. Fruit flies display a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…It has been suggested that the evolutionary pressure applied to the ciliary and flagellar axoneme might affect the architecture of the basal bodies (Carvalho-Santos et al, 2011). Thus, the structural differences we observed might be explained by the special role of the germline centrioles to nucleate the cilium-like projections of the primary spermatocytes, which at the onset of spermatid differentiation elongate in the sperm axoneme (Gottardo et al, 2013;Basiri et al, 2014). However, the female germ cells also have centrioles with triplets (Mahowald and Strassheim, 1970) but lack ciliary projections.…”
Section: Results and Discussion Somatic And Germline Centrioles -Diffmentioning
confidence: 75%
See 2 more Smart Citations
“…It has been suggested that the evolutionary pressure applied to the ciliary and flagellar axoneme might affect the architecture of the basal bodies (Carvalho-Santos et al, 2011). Thus, the structural differences we observed might be explained by the special role of the germline centrioles to nucleate the cilium-like projections of the primary spermatocytes, which at the onset of spermatid differentiation elongate in the sperm axoneme (Gottardo et al, 2013;Basiri et al, 2014). However, the female germ cells also have centrioles with triplets (Mahowald and Strassheim, 1970) but lack ciliary projections.…”
Section: Results and Discussion Somatic And Germline Centrioles -Diffmentioning
confidence: 75%
“…Moreover, the presence of the C-tubule seems to be dispensable in Drosophila for the proper assembly of an axoneme since the sensory cilia of auditory and olfactory sensilla are assembled from basal bodies composed of only doublets. However, when the C-tubule dynamics is defective in unc Drosophila mutants the growth of centrioles and axonemes is severely affected (Gottardo et al, 2013). Thus, at least during Drosophila male gametogenesis, the C-tubule seems to be essential for the proper dynamics of centrioles and to the correct assembly of the ciliary projections.…”
Section: Results and Discussion Somatic And Germline Centrioles -Diffmentioning
confidence: 99%
See 1 more Smart Citation
“…1a,b) (Henneguy, 1898;Meves, 1902;Friedländer and Wahrman, 1970;Wolf andTraut, 1987, Yamashiki andKawamura, 1998). Unlike most animal cells, in which the cilia are reabsorbed to release the centriole that then organizes the spindle poles, the cilium-like projections persist during insect spermatogenesis in order to later organize the sperm axoneme (Riparbelli et al, 2012;Gottardo et al, 2013). Thus, the centriole performs the double role of spindle pole organizer and axoneme constructor.…”
Section: Resultsmentioning
confidence: 99%
“…Testes isolated from pupae were fixed in 2.5% glutaraldehyde in PBS overnight at 4˚C and further processed as described previously (Gottardo et al, 2013). Thin sections were stained routinely with uranyl acetate and lead citrate, and then observed with a Tecnai Spirit EM (FEI) equipped with a Morada CCD camera (Olympus).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%